Minimum wage and tax kink effects in the formal and informal sectors in Zambia - Samuel Bryson; Evaristo Mwale; Kwabena Adu-Ababio (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2024)
This paper explores two policy interventions in Zambia, a minimum wage hike in 2018 and an upward revision in the first kink in the progressive income tax schedule in 2017, to examine and compare the impact of minimum wage and tax kink changes on wages and the earnings distribution in the formal and informal sectors. The analysis builds on two thus far separate strands of literature that investigate the effects of minimum wages and bunching around tax kinks in developing countries using Zambian personal income tax data and data from the ILO Labour Force Surveys over the period 2012-21. Applying the idea that minimum wage effects, despite being targeted at the formal sector, may spill over into the informal sector to tax kinks, this paper proposes a new lighthouse effect-that is, the fact that tax kinks may serve as a reference point for wage setting in the uncovered informal sector. Results show that the minimum wage hike pushes the lower end of the earnings distribution rightward and produces significant and economically meaningful increases in wages in both the formal and informal sectors in Zambia. Interestingly, a hike in the first tax kink produces similar distributional effects and also significantly raises the wages of formal workers in the local earnings distribution around the kink. Combined with evidence of bunching of informal wages at the first and third tax kink, these results suggest that the new lighthouse effect is relevant in the case of Zambia, and underscores the need for policy-makers to take a holistic approach when formulating minimum wage and income tax policies that takes into account spillover effects into the informal sector.
Keywords: H24; J31; J42; 330; bunching; personal income tax; minimum wage; lighthouse effect; informality; Zambia